Latihan plyometric: efektivitasnya dalam meningkatkan daya ledak otot lengan dan tungkai atlet pencak silat remaja - Angga, Prayogi Dwina; Kardiyanto, Deddy Whinata (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Research Problems: Muscle explosive power is one of the dominant physical components in the sport of pencak silat. Research Objective: This study aims to examine the effect of plyometric training in increasing the explosive power of arm and leg muscles in adolescent pencak silat athletes who are members of the Special Athlete Class (KKO) program. Methods: This study is a quasi-experimental study using one-group pretest-posttest. The number of samples involved in this study was 17 adolescent pencak silat athletes who are actively registered in the Special Athlete Class (KKO) program. Arm muscle explosive power was measured through the Medicine Ball Throw Put Test (MBTP), while leg muscle explosive power was measured using the Standing Broad Jump Test. Data analysis used the Shapiro-Wilk normality test and paired sample t-test with a significance level of 0.05. Results: Arm muscle explosive power increased from 2.07 ± 0.24 m to 2.24 ± 0.28 m (t(16) = 6.596; p < 0.001), while leg muscle explosive power increased from 4.51 ± 0.60 m to 5.14 ± 0.83 m (t(16) = 3.607; p = 0.002). The effect sizes obtained were categorized as large (Cohen's d = 1.60 for arm muscles and 0.87 for leg muscles). Conclusion: Plyometric training significantly increased arm and leg muscle explosive power in adolescent pencak silat athletes participating in the Special Sports Class (KKO) program. Plyometric training can be recommended as a form of routine training to optimize the physical capacity and performance of adolescent pencak silat athletes.